Studi variasi genetik hutan alam dan hutan tanaman Pinus merkusii dengan menggunakan teknik isozim=Study of genetic of pinus merkusii natural and plantation forest - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRAK Isozyme analysis was applied to study genetic variation of P. merkusii collected from natural forest (Aceh), plantation forest (Java), and seed orchard (Jember, Java). Genetic variation was examined using seven polimorphic loci from 3 enzyme systems, namely esterase (EST), glutamate oxaloacetate transaminase (GOT), and shikimate dehydrogenase (ShDH). Research result showed that genetic variation in natural population was the highest (He=0,304) comparing to those of plantation forest (He=0,276) and seed orchard (He=0,266). In general, the rate of expected heterozigosity (He) was 0,290. which indicated that P. merkusii had a moderate genetic variation.